PENYULUHAN DAN PEMANTAUAN KESEHATAN IBU HAMIL, TUMBUH KEMBANG BALITA, DAN ANAK PRA SEKOLAH DALAM UPAYA PENURUNAN ANGKA STUNTING DI KABUPATEN PROBOLINGGO - Hermanto, Hermanto; Supraptiningsih, Linda Kurnia; Bahri, Mohammad Saiful; Devi, Nourma Ulva Kumala; Elly, Mohammad Iskak; Putri, Dita Refani; Andayani, Putri; Gholi, Muhammad Al (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
Stunting is one of the main health problems in Probolinggo Regency which has an impact on children's growth and development. The high stunting rate in Probolinggo Regency is a serious problem that requires comprehensive intervention. This community service aims to reduce stunting rates through training in making healthy nutritional menus and implementing healthy kitchens. Training activities involving the community, especially PKK mothers, to increase knowledge and skills in preparing nutritious food menus that suit children's needs. The form of service activity in an effort to reduce stunting rates is through community empowerment through training in making healthy nutritional menus and implementing healthy kitchens. The training involves housewives as the main participants and focuses on increasing knowledge and skills in preparing a balanced menu and maintaining kitchen cleanliness. After this service activity, it is hoped that there will be an increase in community understanding about the importance of balanced nutrition and implementing a healthy kitchen, so that it will have an impact on reducing stunting rates in the areas targeted for training. Keywords: Community Empowerment, Nutrition Training, Healthy Kitchen, Stunting